(untitled) (Research, Society and Development, 2025)
The present study aims to elucidate the importance of performing oral hygiene on hospitalized patients by dental surgeons and how this can directly influence their quality of life during hospitalization. The study was conducted through a narrative literature review. The Intensive Care Unit (ICU) is a hospital area designated for patients who require complex treatments and regular monitoring for their recovery. To maintain patient stability, a multidisciplinary team is essential, including dental surgeons. These professionals stand out for their ability to identify, control, and treat diseases in the oral cavity. Oral health is a key factor for this group, as it is directly linked to overall health, since conditions such as gingivitis and periodontitis can contribute to the onset or worsening of systemic complications, such as bacterial endocarditis and ventilator-associated pneumonia. However, the oral hygiene of ICU patients is often inefficient, and the importance of dental surgeons in these environments remains underrecognized.